Two world views? How regular and reserve Royal Marines perceive each other - Wilkinson, Edith; Kutsch, Elmar; Parry, Emma; Turner, Neil (SAGE, 2023)
Effective integration of the Regular and Reserve Armed Forces is essential to operational effectiveness, but evidence suggests that this remains problematic. Past research has focused on the professional values of Regulars and the perceptions that this group holds about Reservists. In this study, we argue that it is necessary to consider the perceptions of both Regulars and Reservists to truly understand the barriers to integration between these elements of Defence. This study investigates what Regular and Reserve Royal Marines see as the important constructs related to each group, through the use of repertory grid technique with 18 Regulars and 16 Reservists. Not only did the Regulars and Reservists in this study see different constructs as important, they also ascribed different constructs to each group. These differences are potentially problematic when aiming to integrate the Regular and Reserve Armed Forces.
Keywords: integration; construct; Reserve Forces; repertory grid